Self-incompatibility: how plants avoid illegitimate offspring. - Matton, D P (1994)
In some families of flowering plants, a single self-incompatibility (S) locus prevents the fertilization of flowers by pollen from the same plant. Self-incompatibility of this type involves the interaction of molecules produced by the S locus in pollen with those present in the female tissues (pistil). Until recently, the pistil products of the S locus were known in only two families, the Brassicaceae (which includes the cabbages and mustards) and Solanaceae (potatoes and tomatoes). A paper in this issue of the Proceedings describes the molecules associated with self-incompatibility in a third family, the Papaveraceae (poppies). We review current research on self-incompatibility in these three families and discuss the implications of the latest findings in poppy on the likely evolution of self-incompatibility in flowering plants. We also compare research into self-incompatibility with recent progress in understanding the mechanisms by which plants overcome infection by certain pathogens.